ISOLATION OF ROOT NODULE ENDOPHYTES FROM COWPEA (Vigna unguiculata L.) GROWING IN JHUM FIELD IN NAGALAND (INDIA) (Applied Biological Research, 2024)
Legume root nodules are inhabited by numerous symbiotic endophytes which impact the plant growth and development. Cowpea (Vigna unguiculata L.) is one of the most widely grown legume crops in the Jhum fields of Nagaland (India). However, the information on root nodule endophytes of cowpea grown in Jhum (slash and burn) ecosystem is lacking. With the aim to decipher the root nodule micro-symbionts, in the present study, 17 endophytic bacteria were isolated from the root nodules of cowpea. These isolates were clustered into two major groups, constituting eight sub-groups based on RADP-fingerprinting using nif-directed RPO1 primer. Eight unique isolates representing each sub-group were selected for 16S rRNA gene amplification and sequencing. Sequence analysis using BLASTn revealed that these isolates belonged to either Enterobacter or Bacillus species. The presence of these bacteria in root nodules suggests some vital role of non-rhizobial endophytes in the legume root nodule biology.
Keywords: Crop legumes; Jhum field; Root nodule endophytes; RAPD; Vigna unguiculata L.